Scaling up seasonal forecasts to over 2 million users in Senegal - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
With CCAFS support, vital seasonal rainfall forecasts are reaching around two million people across Senegal, helping smallholder farmers make better-informed decisions about agricultural management in a changing climate.